Career Development and Occupational Disease in Chinese Nurses: A Cross-Sectional Study - Wenyu Zhang PhD; Xianzong Ma PhD; Qian Xiao PhD; Shuping Yu PhD; Mingna Zhang RN; Xin Wang RN (SAGE Publishing, 2022)
Background A high tendency of intention to leave has been noted for nurses in China. The nursing profession is currently unstable. Methods A sample of 51406 nurses from 311 hospitals in China who completed the self-administered questionnaire online was recruited via the China Nursing Association by email and phone using a simple random sampling method. The recruitment occurred between July 2016 and July 2017. Results The majority of the nurses had working experience ≤20 years and had to work on night shifts. A high percentage of nurses (71.8%) had insomnia, followed by 37.0% who developed varicose veins and 40.9% who experienced musculoskeletal-related disorders. The proportions of the nurses who developed gastrointestinal and urinary system diseases were 56.0% and 18.2%, respectively. Nearly half of the nurses did not have a clear goal for their future career development and intended to leave. Nurses with long working hours each week were positively associated with the development of occupational diseases. The prevalence of occupational diseases was independently associated with career development. Conclusions A high prevalence of occupational diseases was noted among nurses in China. The data indicated that 50% of the nurses were vague regarding their career planning. The data suggest that managers need to pay more attention and to prevent this problem. Appropriate interventions should also be provided.